Far-infrared radiation and its therapeutic parameters: A superior alternative for future regenerative medicine? - Bo Qin; Shi-jie Fu; Xiong-fei Xu; Jiu-jie Yang; Yuping Wang; Lin-na Wang; Bai-xiong Huang; Jing Zhong; Wan-yu Wu; Heng-ao Lu; Betty Yuen Kwan Law; Nick Wang; et al. (Elsevier, 2024)
In future regenerative medicine, far-infrared radiation (FIR) may be an essential component of optical therapy. Many studies have confirmed or validated the efficacy and safety of FIR in various diseases, benefiting from new insights into FIR mechanisms and the excellent performance of many applications. However, the lack of consensus on the biological effects and therapeutic parameters of FIR limits its practical applications in the clinic. In this review, the definition, characteristics, and underlying principles of the FIR are systematically illustrated. We outline the therapeutic parameters of FIR, including the wavelength range, power density, irradiation time, and distance. In addition, the biological effects, potential molecular mechanisms, and preclinical and clinical applications of FIR are discussed. Furthermore, the future development and applications of FIR are described in this review. By applying optimal therapeutic parameters, FIR can influence various cells, animal models, and patients, eliciting diverse underlying mechanisms and offering therapeutic potential for many diseases. FIR could represent a superior alternative with broad prospects for application in future regenerative medicine.